INTEGRASI, EVALUASI DAN EFEKTIVITAS METODE HALAQAH DALAM BIMBINGAN DAN KONSELING - Afiyah Nurul Aini; Agus Sukirno; Alifah Wardatuljanah; Naila Fitrotu Rohmah (STKIP Subang, 2026)
This article examines the integration, evaluation, and effectiveness of the halaqah method in guidance and counseling (GC) services. Halaqah, as a community-based learning approach rooted in Islamic scholarly tradition, has expanded beyond its origins in pesantren settings and is increasingly being adapted into BK practice across various school types. This study employs a literature review approach by analyzing scientific articles, journals, and books relevant to the topic. The findings indicate that the halaqah method, when integrated into GC services, is capable of promoting students’ self-disclosure, strengthening interpersonal conflict resolution abilities, enhancing emotional intelligence, and facilitating the internalization of positive character values. An evaluation of its implementation reveals supporting and inhibiting factors that counselors must understand before applying this method in the field. Overall, the halaqah method holds significant potential as a contextual, humanistic, and value-based GC service strategy, particularly in educational environments with strong religious orientations.